Individual and Environmental Determinants of the Consumption of Iron-Rich Foods among Senegalese Adolescent Girls: A Behavioural Model - Jérémie B. Dupuis; Aminata Ndène Ndiaye; Nafissatou Ba Lo; El Hadj Momar Thiam; Mohamadou Sall; Sonia Blaney (MDPI AG, 2024)
To improve adolescent nutrition, it is crucial to understand factors underlying food behaviours. This study aims to identify pathways by which the environment and individual factors interact to affect the consumption of iron-rich food (IRF) among Senegalese adolescent girls in the hopes to reduce anemia. This is a cross-sectional study conducted among 600 adolescent girls (10-19 years old) of all 14 regions of Senegal. IRF consumption in the past day and night was evaluated using a food frequency questionnaire. Individual determinants, such as the attitude, the subjected norm, and the perceived behaviour control (PBC), and environmental determinants, such as food accessibility and price, were assessed using a validated and reliable questionnaire. Path analyses were conducted to examine relations between IRF consumption and individual and environmental variables. Overall, 83.7% of girls had the intention to eat IRF and 84.7% reported doing so. The PBC (β = 0.20, p < 0.01) and the attitude (β = 0.57, p < 0.01) predict the intention of consuming IRF daily. In turn, the environment predicts the attitude (β = −0.22, p < 0.01) and the PBC (β = 0.26, p < 0.01). The intention was a predictor of the IRF consumption (β = 0.16, p < 0.05). This research provides guidance to nutrition education programmes as well as to improve the food environment to facilitate the consumption of IRF among adolescent girls by inspiring community health initiatives based on empirical data.